{18-[(2×x-8):3-5]:3+12}:9+12=15
Răspunsuri la întrebare
Răspuns de
11
{18-[(2*x-8):3-5]:3+12}:9=3
18-[(2*x-8):3-5]:3+12=3*9=27
18-[(2*x-8):3-5]:3=27-12=15
18-15=[(2*x-8):3-5]:3
(2*x-8):3-5=3*3=9
(2*x-8):3=14
2*x-8=14*3=42
2*x=50
x=25
18-[(2*x-8):3-5]:3+12=3*9=27
18-[(2*x-8):3-5]:3=27-12=15
18-15=[(2*x-8):3-5]:3
(2*x-8):3-5=3*3=9
(2*x-8):3=14
2*x-8=14*3=42
2*x=50
x=25
Alte întrebări interesante
Limba română,
9 ani în urmă
Engleza,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă